Likert scale vs. visual analogue scale on vehicle seat discomfort questionnaire: a review - Mohammad Yusof, Nur Athirah Diyana; Mohamad Jamil, Putri Anis Syahira; Hashim, Nurul Maizura; Karuppiah, Karmegam; Rasdi, Irniza; Mohd Tamrin, Shamsul Bahri; How, Vivien; Sambasivam, Sivasankar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Discomfort measurement has usually been attempted by asking the participants to rate the scale of their discomfort which commonly termed as a subjective scale. Various studies had conducted the discomfort level on vehicle seat by using Visual Analogue Scale (VAS) and Likert scale. VAS is a tool that use to measure a discomfort or characteristics in range across a continuum of values. Meanwhile, Likert-scale is a tool consist of items that require respondents to rate their degrees of comfort or discomfort with various declarative statements. Thus, the purpose of this study is to review, discuss and compare between the VAS and Likert scale used on the development and assessment of sitting discomfort survey in seat vehicles. The literature on various topics related to questionnaire development on discomfort in seat vehicle were collected from electronic databases. Four high-quality studies were eligible and met the inclusion and exclusion criteria. Overall, there is no evidence and conclusion that neither visual analogue scale nor Likert scale are better to one another. Therefore, it can be concluded that either of this scale still applicable for the ergonomic research application as both of this scale have their own pros and cons.